The Role of Spirituality in the Success of Elderly Developmental Tasks: Integrity vs Despair Stage at Wisma Harapan Asri - Siti Hikmah Anas; Fenita Indriani; Anggi Oktafia; Nurul Khoirunnisa Ar-Rohmah; Masnu’atul hariroh; Anjani Rifka Dewi; Ilham Pramudya; Soviyatun Nur Hikmah; Suraida Haya (Tinta Emas Institute, 2025)
This study aims to explore the role of spirituality in the completion of psychosocial developmental tasks of the elderly at the stage of integrity versus hopelessness as described in Erik Erikson's theory. A qualitative approach with a phenomenological design was used to understand the meaning of the spiritual experiences of the elderly living in Wisma Harapan Asri. Data collection techniques were conducted through semi-structured interviews and observation, then analyzed using thematic analysis techniques. The results of the thematic analysis show that spirituality plays an important role in achieving self-integrity, as seen from self-acceptance, wisdom, meaning of life, and readiness to face death. Participants indicated that the practice of worship, closeness to God, and reflection on the meaning of life helped them manage physical limitations, feelings of loneliness, and existential uncertainty. The findings confirm that spirituality is not just a religious activity, but a foundation of psychological resilience that strengthens older adults' mental well-being and acceptance of the past and end of life. This study contributes to gerontological psychology by emphasizing the importance of psychospiritual interventions in supporting older adults in institutional settings.